Consequence of anchoring holes technique on the bond behavior between CFRP composites and heat-damaged concrete. (October 2020) - Al-Rousan, Rajai Z.; AL-Tahat, Mohammad F.
Abstract: Exposure of concrete structures to elevated temperatures causes a sever deterioration because of decomposition of cement hydration products, generation of vapor pressure and the inhomogeneous volume changes of concrete's ingredients and beyond a temperature of 500 °C. The most Retrieval the structural performance of severely heat-damaged structural concrete members would be most significantly achieved using carbon fiber-reinforced polymer (CFRP) composite materials. Therefore, an experimental study investigated the influence of special anchoring holes on the bond-slip behavior between CFRP composites and concrete exposed to elevated temperatures. For this purpose, one ninety six concrete prisms (150 × 150 × 200 mm) were casted with different drilling hole diameter (0 mm: None, 6 mm, 10 mm, 14 mm), CFRP sheet bonded length (65 mm, 90 mm, 115 mm) and exposed to elevated temperature (23 °C, 250 °C, 500 °C, 750 °C). The bonding surface of each concrete blocks was prepared and then anchoring holes were drilled using rotary drill. The experimental results showed that the anchoring drilling hole diameter has a significant effect on the bond-slip behavior. In general, both the bond strength and ultimate slippage decrease as the temperature increases as well as increase as the drilling hole diameter increases and as the CFRP sheet length increase. The considerable reductions in residual compressive and splitting strengths at temperatures greater than 500 °C was reflected negatively on bond slip behavior for the tested specimens; represented in a reduction in ultimate bond force and slippage at failure to 67% and 19% of control values, respectively. Bond failure of specimens without anchored holes was categorized by skin peeling and as the number of anchored drilled holes and temperature increases the failed adhesion surface shows more concrete remained attached to the CFRP composite indicating a stronger bonding. The special feature of the present study is that the new bond–slip model is proposed and based on anchored hole CFRP composite and concrete exposed to elevated temperature; instead, the existing bond–slip models are based on un-anchored CFRP composite and concrete treated under room temperature. This new model is then assessed using experimental test results and existing bond–slip models in the literature published by several researchers. Finally, the new bond–slip model is provided a precise prediction of bond force and slippage at failure for concrete elements affected by post-heating damage hence should be accounted for when designing for repairing.